HUBUNGAN ANTARA PERSEPSI PASIEN RAWAT INAP TENTANG KUALITAS PELAYANAN KESEHATAN DENGAN CITRA RUMAH SAKIT ISLAM SITI HAJAR MATARAM - Hakim, Faradila Khoirun Nisa; Ekawanti, Ardiana; Syamsun, Arfi (Faculty of Medicine Universitas Mataram, 2013)
Background: Hospital is a health facility that serve as a place of healing and restoration of health. The success rate of a hospital is usually evaluated in term of the utilization of facilities, quality and level of service efficiency. Since Moslems Hospital of Siti Hajar Mataram is one of the oldest private hospital in the city of Mataram and it had a great patient’s volume, the researchers intend to follow through with doing research on the relationship between patients’s perception about health care quality in inpatient care and the image of Moslems Hospital of Siti Hajar Mataram. Methods: A cross-sectional study was performed using consecutive sampling. The participants recruited were patients admitted to inpatient care in the Moslems Hospital of Siti Hajar Mataram. Data were collected using questionnaire. A pilot test was done to evaluate validity and reliability of the questionnaire prior to data collection. Data were analysed with descriptive analysis; bivariate analysis using spearman method; and multivariate analysis using multiple linear regression to determine the effect on the health care quality toward hospital’s image. Results: Multivariate analysis showed that the variable quality of medical services, supporting examinations, nurses, administration and management significantly affected the image. Administrative and management service was the most dominant variable. Based on the results of the ANOVA test, p-value obtained was 0,000. Adjusted R2 value obtained was 0.634, indicating that the equations was good discrimination. Conclusion: There is a relationship between the quality of medical services, supporting examination, nurses, administration and management with the image of Moslems Hospital of Siti Hajar Mataram. Keywords: Patient perception, Inpatient care, Health Care Quality, Image of Hospital.